Genetic variations in the Myostatin gene affecting growth traits in sheep - Noha M. Osman; Heba I. Shafey; Mohamed A. Abdelhafez; Ahmed M. Sallam; Karima F. Mahrous (Veterinary World, 2021)
Background and Aim: Sheep productivity in developing countries is crucial, as this animal is an essential source of meat and wool. Myostatin (MSTN) plays an important role in the regulation of muscle mass through the regulation of muscle growth, differentiation, and regeneration. The present study sought to investigate genetic variation in the first intron of the MSTN gene and the association of variants with growth traits in major sheep breeds in Egypt (Barki, Ossimi, and Rahmani) and Saudi Arabia (Najdi) using polymerase chain reaction (PCR) and sequencing.